Nilai-Nilai Kearifan Lokal dalam Sajak Ziarah Karya Abdul Wachid B.S. - Wahyu Budiantoro (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2018)
The purpose of this research is to identify the values of local wisdom in the poetry of pilgrimage (visiting graves) written by Abdul Wachid B.S. The relevance of the local wisdom with the literature has been already started since the era of Sheikh Hamzah Fansuri. He investigated the territory of his homeland to be developed as the aesthetical value of his poetry. Beside of Sheikh Hamzah Fansuri, there are some other names like Sunan Bonang, Sunan Kalijaga, and R. Ng. Ranggawarsita. In this study, the subject was the poet called Abdul Wachid B.S., while the object is the poem entitled the pilgrimage. Through the rhymes, the local wisdom values in the poetry of Abdul Wachid B.S. can be identified. The results of this study indicate some values of local wisdom in the poetry of pilgrimage authored by Abdul Wachid B.S., among others are: the first, Abdul Wachid B.S. interpreted the value of local wisdom as an effort to build the shape or sound of the poetry in terms of the aesthetical basis (language). The second, in addition to the aesthetical basis (language), Abdul Wachid B.S. interpreted the local wisdom philosophically. Abdul Wachid B.S. philosophy in the poetry of pilgrimage is attempted to examine the wisdom of those historical circumstances related to Islam. The third, the value achieved from the poetry of Abdul Wachid B.S. pilgrimage is as an effort to search for the sanad, in order to find the genealogy of the science or the transformation of the vision of Islam in daily life.